Diagnostics and monitoring of overtraining in sport- a review of the literature - Sonia Biesiada; Anna Maria Dobosiewicz (Kazimierz Wielki University, 2017)
Overtraining is a common phenomenon that occur in the sport, which is formed by: disregard the effects of fatigue, misreading the decline in exercise capacity or stagnation and disorder of the relationship between training and rest. It consist in reduction or loss of form by the athlete, can also contribute to the formation of an injury and adversely affect the psyche of the athlete.   The mechanism of the formation of the overtraining syndrome is not conclusive, since this phenomenon is characterized by a variety of symptoms that may indicate other diseases or infections. Therefore, the diagnosis of overtraining syndrome can be made only by eliminating other influence on the change of form and mood, because there is no diagnostic tools, with which those instruments would be the identification of the OTS. An overtraining syndrome is diagnosed if you exclude all the rest. Because of difficulties encountered by the diagnosis of overtraining prevention is important. It is the best way to avoid this phenomenon. The behavior of moderation in the training, the appropriate time for the regeneration of the body, using a detailed training plan, coachs and sports doctors collaboration , proper diet, psychological support and training log are the clue factors.